Case report: Right atrial appendage hybrid access to bailout a stuck stent from the inferior vena cava of a small child - Prakoso, Radityo; Sembiring, Aditya Agita; Hernisa, Latifa; Mendel, Brian; Lelya, Olfi; Lilyasari, Oktavia (Frontiers in Cardiovascular Medicine, 2023)
A three-month-old baby boy (5. 4 Kg) with pulmonary atresia, subaortic ventricular septal defect (VSD), and patent ductus arteriosus (PDA) was sent for ductal stenting from the femoral vein. The route to the PDA was extremely tortuous and the procedure was complicated with a stent stuck in the abdominal inferior vena cava (IVC). Transfemoral stent recapture was technically laborious and the stent was successfully recaptured across a 10-Fr right atrial appendage (RAA) hybrid access avoiding a cardiopulmonary bypass (CBP). The PDA was subsequently stented for the femoral artery with satisfactory clinical outcomes.